2004
DOI: 10.1074/jbc.m407478200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Histone Acetyl Transferase Tip60 in the p53 Pathway

Abstract: The histone acetyl transferase Tip60 (HTATIP) shares many properties with the tumor suppressor p53 (TP53). Both proteins are involved in the cellular response to DNA damage, are subjected to proteasomal digestion following Mdm2-mediated ubiquitination, and accumulate after UV irradiation. We found here that knock-down of Tip60 affects the p53-dependent response following actinomycin D treatment, most likely because it inhibits p21 (CDKN1A) accumulation. Moreover, Tip60 is required for p53 to activate the endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
140
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(155 citation statements)
references
References 33 publications
15
140
0
Order By: Relevance
“…To assess the function of TIP60 in UV-induced DNA damage response, we introduced siRNA oligonucleotides to suppress TIP60 protein level. As reported previously (for example, Legube et al, 2004), the siRNA duplexes suppress TIP60 protein accumulation ( Figure 4A). …”
Section: Uv Irradiation Induces the Sumoylation Of Tip60 At Lysines 4supporting
confidence: 89%
See 2 more Smart Citations
“…To assess the function of TIP60 in UV-induced DNA damage response, we introduced siRNA oligonucleotides to suppress TIP60 protein level. As reported previously (for example, Legube et al, 2004), the siRNA duplexes suppress TIP60 protein accumulation ( Figure 4A). …”
Section: Uv Irradiation Induces the Sumoylation Of Tip60 At Lysines 4supporting
confidence: 89%
“…ATR/Chk2 phosphorylates p53 at Ser 20 and stabilize p53 protein levels (for example, Legube et al, 2004). Sun et al (2005) demonstrated that TIP60 HAT activates ATM autophosphorylation in response to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with its function in histone acetylation, Tip60 is mainly involved in transcriptional activation of specific genes (Gaughan et al, 2001;Berns et al, 2004;Legube et al, 2004). Transcriptional regulation of some genes, such as E2F or c-mycdependent genes, most likely involves the whole Tip60 complex (Frank et al, 2003;Taubert et al, 2004).…”
Section: Introductionmentioning
confidence: 87%
“…As in many other cancer cells, TSA treatment strongly induces apoptosis ( Figure 3a). Importantly, this apoptosis is inhibited by siRNA directed against Tip60 (described in Legube et al (2004) and Tyteca et al (2006)), indicating that Tip60 expression is, at least in part, required for TSA-induced apoptosis (the efficiency of the knockdown was checked by western blot and RT-QPCR ( Figure 3b). This result thus shows that the Tip60-dependent apoptotic pathways are functional in these cells and that activating endogenous Tip60 function is sufficient to promote apoptosis.…”
Section: Tip60 Function Is Rate Limiting For Apoptosis In Hct116 Cellsmentioning
confidence: 99%